2021
DOI: 10.1111/tpj.15568
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting the soil microbiota

Abstract: SUMMARY Soil is a living ecosystem, the health of which depends on fine interactions among its abiotic and biotic components. These form a delicate equilibrium maintained through a multilayer network that absorbs certain perturbations and guarantees soil functioning. Deciphering the principles governing the interactions within soils is of critical importance for their management and conservation. Here, we focus on soil microbiota and discuss the complexity of interactions that impact the composition and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 147 publications
0
26
0
2
Order By: Relevance
“…Strict hygrophiles are principally associated with Acidobacteriota , Bacteroidota , and Proteobacteria . In ecological and biological terms, it is not surprising that a soil without water restriction presents a variety of microorganisms ( 88 ). However, a study focusing on fungi (internal transcribed spacer [ITS]) could provide more information on the diversity and soil pressure associated with strict hygrophiles as these appear to be more sensitive indicators of soil water content than bacteria ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strict hygrophiles are principally associated with Acidobacteriota , Bacteroidota , and Proteobacteria . In ecological and biological terms, it is not surprising that a soil without water restriction presents a variety of microorganisms ( 88 ). However, a study focusing on fungi (internal transcribed spacer [ITS]) could provide more information on the diversity and soil pressure associated with strict hygrophiles as these appear to be more sensitive indicators of soil water content than bacteria ( 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed that soil water content showed a significant negative correlation with the fungal Chao1 index ( Figure S3 ). Similarly, the effect of SWC on fungal diversity was also reported in other forest ecosystems, such as the forests in western Canada [ 57 ] and eastern China [ 58 , 59 ] This may be because soil water content influences the O 2 level in the soil and affects soil nutrient availability and transportation [ 29 ], which in turn structures soil fungal metabolic pathways and community composition [ 60 ].…”
Section: Discussionmentioning
confidence: 85%
“…Soil microbial communities are considered essential for maintaining soil health and promoting healthy plant growth [ 75 77 ], but agricultural intensification and modern agriculture management practices can have lasting effects on the soil microbiome [ 5 , 17 , 78 ]. In this study, the legacy effects of metam sodium (MS) on soil microbial communities and their response to MS application were examined.…”
Section: Discussionmentioning
confidence: 99%